2020
DOI: 10.1111/bjh.17273
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor propeptide in severe coronavirus disease 2019 (COVID‐19): evidence of acute and sustained endothelial cell activation

Abstract: Summary Endothelial cell (EC) activation plays a key role in the pathogenesis of pulmonary microvascular occlusion, which is a hallmark of severe coronavirus disease 2019 (COVID‐19). Consistent with EC activation, increased plasma von Willebrand factor antigen (VWF:Ag) levels have been reported in COVID‐19. Importantly however, studies in other microangiopathies have shown that plasma VWF propeptide (VWFpp) is a more sensitive and specific measure of acute EC activation. In the present study, we further invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 19 publications
8
113
0
5
Order By: Relevance
“…Mounting evidence has shown that SARS-CoV-2 can directly target endothelial cells [48][49][50][51][52][53][54][55][56][57], an aspect initially reported by our group in March 2020 by simply observing the systemic manifestations in COVID-19 patients [48,49,58], and later corroborated by autoptic findings [59][60][61][62][63] and by the analysis of amputation specimens [64]. Intriguingly, brain endothelial cells show a distinct pro-inflammatory response when exposed to SARS-CoV-2 spike protein subunits [65] and infected vascular endothelial cells have been shown to spread SARS-CoV-2 to glial cells in the central nervous system [66].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that SARS-CoV-2 can directly target endothelial cells [48][49][50][51][52][53][54][55][56][57], an aspect initially reported by our group in March 2020 by simply observing the systemic manifestations in COVID-19 patients [48,49,58], and later corroborated by autoptic findings [59][60][61][62][63] and by the analysis of amputation specimens [64]. Intriguingly, brain endothelial cells show a distinct pro-inflammatory response when exposed to SARS-CoV-2 spike protein subunits [65] and infected vascular endothelial cells have been shown to spread SARS-CoV-2 to glial cells in the central nervous system [66].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the VWFpp/VWF:Ag ratio dropped as VWF clearance was reduced and this is thought to lead to the elevated plasma VWF:Ag levels seen in severe COVID-19. Thus, VWFpp levels constitute a more sensitive and specific measure of acute EC activation [20,21] encountered in these severe COVID-19 cases [19]. Furthermore, VWF:Ag, VWF ristocetin cofactor (RCo), and VWFpp levels elevated in accordance with disease severity while levels of A Disintegrin And Metalloprotease with ThromboSpondin 1 repeats, number 13 (ADAMTS13) concordantly decreased [22].…”
Section: Covid-19-associated Endothelial Dysfunction and Thromboinflammationmentioning
confidence: 91%
“…Słomka et al summarized the hematological manifestations in COVID-19 and several studies have shown hematological parameters are markers of disease severity [18]. Especially for blood coagulation, a recent study revealed that plasma von Willebrand factor antigen (VWF:Ag) and pro-coagulant factor VIII (FVIII) levels, as well as plasma VWF propeptide (VWFpp), markedly increased in COVID-19 patients [19]. Additionally, the VWFpp/VWF:Ag ratio dropped as VWF clearance was reduced and this is thought to lead to the elevated plasma VWF:Ag levels seen in severe COVID-19.…”
Section: Covid-19-associated Endothelial Dysfunction and Thromboinflammationmentioning
confidence: 99%
“…Age is strongly associated with disease severity, with older individuals suffering poorer outcomes (4,5). The immunological changes associated with severe disease are also known, with increased inflammatory proteins, coagulopathy and changes in myeloid cell populations reported (6)(7)(8). In particular, severe COVID-19 is characterised by expansion of immature myeloid populations, with loss of HLA-DR expression by monocytes and loss of CD10 expression on neutrophils (9,10).…”
Section: Introductionmentioning
confidence: 99%